What Did Chaplains Do During the Covid Pandemic? An International Survey - Snowden, Austyn (Journal of pastoral care & counseling, 2021)
Chaplains’ unique contribution is to healthcare is to respond to the spiritual, religious and pastoral needs of patients and staff. This is their sole purpose, to provide a presence and space to meet individual need and promote healing, even when cure isn’t possible. Their value is priceless to families in desperate times. However, despite growing evidence for their impact, chaplains are commonly undervalued and misunderstood by their organisations, and the global pandemic revealed the consequences of this confusion. Whilst some chaplains were applauded as heroes along with their fellow health colleagues, others were seen as little more than an infection risk. A survey was designed to capture and learn from the full range of chaplain experiences of the impact of the pandemic across the globe. In June 2020, 1657 chaplains responded from 36 countries. They all experienced considerable disruption to their usual practice, with enforced social distancing having the biggest impact. Out of necessity they embraced technology to maintain contact with patients and families, and shifted focus of their support to staff. Whilst some chaplains were viewed as essential employees by their organisations, most were not. Despite the majority thinking that their organisations understood what they did, chaplains themselves were neither clear or unclear about their role during and post pandemic. More surprisingly, they felt similarly unclear about their role before the pandemic. This paper concludes that in general chaplains lack leadership skills, and confusion about their role will persist until this changes.